Parental supply of alcohol and adolescent drinking: a multilevel analysis of nationally representative data - Gary C. K. Chan; Janni Leung; Jason Connor; Wayne Hall; Adrian B. Kelly (BMC, 2017)
Abstract Background Existing research on parental supply of alcohol analyses the effects of self-reported parental supply on adolescent drinking using individual level data. This study examined the contextual effect of parental supply of alcohol on adolescent alcohol use by examining the association between the prevalence of parental supply in each Australian state and adolescent alcohol use using a multilevel analytic framework. Methods Adolescent samples (Age: 12-17) were drawn from the four National Drug Strategy Household Surveys (2004, 2007, 2010 and 2013; N = 6803). The prevalence of parental supply of alcohol, defined as the weighted percentage of sample who reported obtaining alcohol from their parents, was estimated in each state and territory across the four surveys. Three multilevel logistic regressions were used to examine the contextual effects of parental supply prevalence on adolescents' alcohol use in the past 12 months, weekly drinking and heavy drinking. Results Overall, adolescents' rates of past 12 months alcohol use, heavy drinking and weekly drinking between 2004 and 2013 were 40.1, 14.4 and 6.4% respectively. The prevalence of parental supply was significantly associated with past 12 months alcohol use (OR = 1.06, p < .001) and heavy drinking (OR = 1.04, p < .001) but not with weekly drinking (OR = 1.03, p = .189). The results were adjusted for gender, age, socio-economic index for area, place of birth, survey year and prevalence of peer supply. Conclusion A high prevalence of parental supply in a region was associated with heavier adolescent drinking, regardless of whether adolescents primarily obtained their alcohol from their own parents.